Safety and Immunogenicity of a Respiratory Syncytial Virus Prefusion F Vaccine When Coadministered With a Tetanus, Diphtheria, and Acellular Pertussis Vaccine. (12th October 2021) - Peterson, James T; Zareba, Agnieszka M; Fitz-Patrick, David; Essink, Brandon J; Scott, Daniel A; Swanson, Kena A; Chelani, Dhawal; Radley, David; Cooper, David; Jansen, Kathrin U; Dormitzer, Philip R; Gruber, William C; et al.
Abstract: Background: Prevention of respiratory syncytial virus (RSV) disease in infants is an unmet vaccine need, and maternal immunization is a potential strategy to address this need. This study evaluated concomitant administration of RSV stabilized prefusion F subunit vaccine (RSVpreF) and tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis vaccine adsorbed (Tdap) in healthy, nonpregnant women 18‒49 years of age. Methods: In this phase 2b, multicenter, placebo-controlled, observer-blind, noninferiority study, participants were randomized to receive RSVpreF in a range of doses and formulations with Tdap or alone, or Tdap alone. Safety and immunogenicity were assessed. Results: Local reactions and systemic events were generally similar across vaccine groups. Noninferiority of anti-RSV-A and anti-RSV-B immune responses induced by RSVpreF with Tdap was demonstrated compared to RSVpreF alone. Noninferiority of anti-diphtheria toxoid and anti-tetanus toxoid immune responses after administration of RSVpreF with Tdap was demonstrated compared to Tdap alone; noninferiority was not met for anti-pertussis component responses. Conclusions: RSVpreF was safe and well tolerated when administered with Tdap or alone in nonpregnant women 18‒49 years of age. Immune responses induced by Tdap administered with RSVpreF were noninferior for the tetanus and diphtheria components of Tdap, but not for pertussis. Clinical Trials Registration: NCT04071158. Abstract : Respiratory syncytial virus stabilized prefusion F subunit vaccine (RSVpreF) was safe and well tolerated when administered with Tdap or alone in nonpregnant women. Tdap-induced immune responses with concomitant RSVpreF were noninferior for tetanus and diphtheria, but not the pertussis component.